Surgery around the Orbit: How to Select an Approach - Locatelli, Davide; Dallan, Iacopo; Castelnuovo, Paolo (Journal of Neurological Surgery Part B: Skull Base, 2020)
Orbital region pathologies may be safely and effectively treated through a various number of approaches. As the concept of “outcome” and minimally invasive surgery keeps gaining popularity in neurosurgery, these approaches—each with specific indications and limitations—together provide the best surgical options.
Keywords: orbital surgery; assisted endoscopic surgery; endoscopy; orbital tumors; superior eyelid approach; inferior eyelid approach; endonasal orbital approach